A comparative study of bubble formation characteristics in non-Newtonian and high-viscosity Newtonian fluids by a laser image technique. Issue 10 (2nd August 2021) - Fan, Wenyuan; Zhang, Xi; Du, Mengqi; Li, Shuaichao; Yin, Xiaohong
Abstract: A laser image measurement system has been established to study the problem of dynamic bubble formation from a submerged orifice in two kinds of high-viscous fluids, namely Newtonian glycerol aqueous solution and non-Newtonian carboxymethylcellulose (CMC) aqueous solutions. The bubble generation process was measured accurately by means of He-Ne laser as light source using the beam expanding and light amplification technology. The whole formation process, including bubble expansion, stretching and detachment three stages, and the dynamic characteristics of each stage, were investigated experimentally by analyzing comparatively the evolution of the instantaneous shape, volume, surface area, and deformation rate in both fluids. The influences of solution mass concentration, gas chamber volume and orifice diameter on bubble detached volume were discussed respectively, and the results reveals that bubble begins to grow spherically due to the predominant role of surface tension, and then is elongated gradually owing to the increasing buoyancy force. Compared with Newtonian fluid, bubble formed in non-Newtonian fluid presents a slim shape as a result of the shear-thinning effect of CMC solution. Bubble detachment volume in both kinds of fluids increases with solution mass concentration and gas chamber volume, but declines with orifice inner diameter, respectively. Graphical Abstract: